2017
DOI: 10.1038/s41598-017-13842-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term aspirin use on molecular alterations in precancerous gastric mucosa in patients with and without gastric cancer

Abstract: The risk of gastric cancer (GC) remains even after H. pylori eradication; thus, other combination treatments, such as chemopreventive drugs, are needed. We evaluated the effects of aspirin on genetic/epigenetic alterations in precancerous conditions, i.e., atrophic mucosa (AM) and intestinal metaplasia (IM), in patients with chronic gastritis who had taken aspirin for more than 3 years. A total of 221 biopsy specimens from 74 patients, including atrophic gastritis (AG) cases without aspirin use (control), AG c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(48 citation statements)
references
References 60 publications
4
43
1
Order By: Relevance
“…This procedure (i.e., LCM), might provide more information from atrophic or IM glands than would the use of whole tissue material with regard to gastric carcinogenesis in the precancerous conditions. 32,37,38,92 Although it has been reported that miR-124a-3 and miR-34b/c methylations in the background mucosa were associated with an increased risk of developing MGCs, 33,34,48,49 in our previous study the methylations of miR-124a-3 and miR-34c were mostly observed in IM, and only rarely in atrophy. 38 Thus, these results indicate that the methylation of these miRNA genes might be a specific marker expressed in IM and might not necessarily be a risk marker for GC.…”
Section: Problems Of Molecular Analysis In Precancerous Conditionsmentioning
confidence: 56%
See 4 more Smart Citations
“…This procedure (i.e., LCM), might provide more information from atrophic or IM glands than would the use of whole tissue material with regard to gastric carcinogenesis in the precancerous conditions. 32,37,38,92 Although it has been reported that miR-124a-3 and miR-34b/c methylations in the background mucosa were associated with an increased risk of developing MGCs, 33,34,48,49 in our previous study the methylations of miR-124a-3 and miR-34c were mostly observed in IM, and only rarely in atrophy. 38 Thus, these results indicate that the methylation of these miRNA genes might be a specific marker expressed in IM and might not necessarily be a risk marker for GC.…”
Section: Problems Of Molecular Analysis In Precancerous Conditionsmentioning
confidence: 56%
“…Our previous study also showed that long-term aspirin use (≥3 years) was associated with a significant reduction of CDH1 methylation in atrophy (OR, 0.15; 95% CI, 0.06 to 0.41; p=0.0002), but was less effective in reversing the methylation that occurred in IM. 37 MSI did not change significantly after taking aspirin in either patient with atrophy or those with IM. 37 Interestingly, CIMP in IM, which is a surrogate marker of GC, 38 decreased in patients with chronic gastritis who regularly took aspirin for more than three years.…”
Section: Effects Of Aspirin On Molecular Eventsmentioning
confidence: 74%
See 3 more Smart Citations